The Medical Education Partnership Initiative (MEPI): Innovations and Lessons for Health Professions Training and Research in Africa - Francis Omaswa; Elsie Kiguli-Malwadde; Peter Donkor; James Hakim; Miliard Derbew; Sarah Baird; Seble Frehywot; Onesmus Wairumbi Gachuno; Steve Kamiza; Isaac Ongubo Kibwage; Alfred Mteta Kien; Yakub Mulla; et al. (Ubiquity Press, 2018)
MEPI was a $130 million competitively awarded grant by President's Emergency Plan for AIDS Relief (PEPFAR) and National Institutes of Health (NIH) to 13 Medical Schools in 12 Sub-Saharan African countries and a Coordinating Centre (CC). Implementation was led by Principal investigators (PIs) from the grantee institutions supported by Health Resources and Services Administration (HRSA), NIH and the CC from September, 2010 to August, 2015. The goals were to increase the capacity of the awardees to produce more and better doctors, strengthen locally relevant research, promote retention of the graduates within their countries and ensure sustainability. MEPI ignited excitement and stimulated a broad range of improvements in the grantee schools and countries. Through in-country consortium arrangements African PIs expanded the programme from the 13 grantees to over 60 medical schools in Africa, creating vibrant South-South and South-North partnerships in medical education, and research. Grantees revised curricular to competency based models, created medical education units to upgrade the quality of education and established research support centres to promote institutional and collaborative research. MEPI stimulated the establishment of ten new schools, doubling of the students' intake, in some schools, a three-fold increase in post graduate student numbers, and faculty expansion and retention. Sustainability of the MEPI innovations was assured by enlisting the support of universities and ministries of education and health in the countries thus enabling integration of the new programs into the regular national budgets. The vibrant MEPI annual symposia are now the largest medical education events in Africa attracting global participation. These symposia and innovations will be carried forward by the successor of MEPI, the African Forum for Research and Education in Health (AFREhealth). AFREhealth promises to be more inclusive and transformative bringing together other health professionals including nurses, pharmacists, and dentists.